Video for change : a guide for advocacy and activism - Gregory, Sam (Pluto Press in association with Witness, 2005)
--This is the first ever comprehensive practical guide to human rights and video campaigning--Pictures from Abu Ghraib showed the power of the amateur image to grab the world's attention. The Asian tsunami, caught on camcorder, brought home the reality.